1984
DOI: 10.1002/clc.4960071205
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of high‐dose verapamil and diltiazem in the long‐term treatment of stable exertional angina

Abstract: Summary:The efficacy and safety of highdose verapamil (480 mg/day) and diltiazem therapy (360 mg/day) were compared in separate cohorts of 26 and 20 patients, respectively. All patients had stable exertional angina and underwent an initial 6-week double-blind, placebocontrolled, randomized phase followed by a 12-month open-label period. Angina attacks were reduced by veraparml(6.3 f7.5 to 2.5 f4.1 attacks per week, p <0.001) and by diltiazem (9.2f7.5 to 3.0f3.1 attacks per week, p <0.001), while treadmill time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Apart from that conducted by Weiner et al (1984), trials comparing diltiazem with other calcium antagonists in patients with effort angina have been of relatively short duration (table VII). Several double-blind studies have shown diltiazem to be more effective than nifedipine in reducing the frequency of anginal attacks and increasing the number of pain-free days (Frishman et al 1988;Klinke et al 1988;Pagliano 1985).…”
Section: Comparison and Use In Combination With Other Calcium Antagonmentioning
confidence: 99%
“…Apart from that conducted by Weiner et al (1984), trials comparing diltiazem with other calcium antagonists in patients with effort angina have been of relatively short duration (table VII). Several double-blind studies have shown diltiazem to be more effective than nifedipine in reducing the frequency of anginal attacks and increasing the number of pain-free days (Frishman et al 1988;Klinke et al 1988;Pagliano 1985).…”
Section: Comparison and Use In Combination With Other Calcium Antagonmentioning
confidence: 99%
“…Comparative studies of diltiazem, nifedipine and verapamil are few but in those that have been undertaken the efficacy of all three compounds has been found to be comparable (54). When comparing single doses of diltiazem, nifedipine and propranolol, however, diltiazem has been shown to improve exercise tolerance over a longer period of time (55).…”
Section: Clinical Assessmentmentioning
confidence: 99%